EFEKTIVITAS INTERVENSI LEE SILVERMAN VOICE TREATMENT (LSVT) BIG DALAM MENINGKATKAN KESEIMBANGAN PADA KASUS STROKE - Retna Febri Arifiati; Endang Sri Wahyuni (Tahta Media Group, 2024)
Stroke is a sudden loss of brain function and triggers unilateral paralysis which can reduce posture and balance control, resulting in difficulty walking. This study aims to determine the effectiveness of LVST-BIG training in improving balance in stroke cases. Based on pre-experimental quantitative research with a one-group pretest-posttest design, this research population took stroke cases in Dibal Village, Ngemplak District, Boyolali with a total sampling technique of 7 people. This intervention was carried out in stroke cases 16 times with a duration of 30 minutes/session. The balance measuring tool uses the Berg Balance Scale instrument. Hypothesis testing using Paired Samples T Test. The results of the research obtained a significance value of 0.000<0.05 which shows that there is a difference in the mean results of the Berg Balance Scale between groups before being given intervention or after being given intervention for stroke conditions in Dibal Village, Ngemplak Boyolali